Hours Constraints and Wage Differentials across Firms - Claudio Labanca; Dario Pozzoli (Institute of Labor Economics (IZA), 2022)
Although constraints on hours worked at the firm-level are viewed as an important determinant of firm wages, little direct evidence exists to support this view. In this paper, we use linked employer-employee data on hours worked in Denmark to measure hours constraints and to investigate how these constraints relate to firm wages. We show that firms with stricter constraints pay higher firm-specific wages and that these premiums are concentrated in more productive firms. Starting from these findings we discuss a framework in which hours constraints are motivated by the productivity gains derived from having a more cooperative production process, leading more productive firms to constrain hours and to pay compensating wage differentials.
Keywords: J31; J33; 330; wage differentials; hours constraints; cooperation